Randomised, open-label, non-inferiority clinical trial on the efficacy and safety of a 7-day vs 14-day course of antibiotic treatment for uncomplicated enterococcal bacteraemia: the INTENSE trial protocol - Jesús Rodríguez-Baño; Zaira R Palacios-Baena; Clara M Rosso-Fernández; Natalia Maldonado; Elena Salamanca; Luis Eduardo López-Cortés; Irene Borreguero Borreguero; Inés Portillo-Calderón; Enriqueta Tristán-Clavijo; Felipe Fernández-Cuenca; Marina De-Cueto; Emilio Stolz-Larrieu (BMJ Open, 2023)
Introduction Enterococcus spp is responsible for 8%–15% of total bacteraemias with an associated global mortality around 23%–30%. Regarding the clinical management of enterococcal bacteraemia, the evidence on the duration of antibiotic treatment is scarce and the studies do not discriminate between complicated and uncomplicated bacteraemia.Methods The INTENSE study is a multicentre, open-label, randomised, pragmatic, phase-IV clinical trial to demonstrate the non-inferiority of a 7-day vs 14-day course for the treatment of uncomplicated enterococcal bacteraemia and incorporating the early switching to oral antibiotics when feasible. The primary efficacy endpoint is the clinical cure at day 30±2 after the end of the treatment. Secondary endpoints will include the rate of relapse or infective endocarditis, length of stay, duration of intravenous therapy, Clostridioides difficile infection and the evaluation of the safety of both treatment arms through the recording and analysis of adverse events. For a 6% non-inferiority margin and considering a 5% withdrawal rate, 284 patients will be included.Analysis The difference in proportions with one-sided 95% CIs will be calculated for the clinical cure rate using the control group as reference. For secondary categorical endpoints, a similar analysis will be performed and Mann-Whitney U-test will be used to compare median values of quantitative variables. A superiority analysis applying the response adjusted for days of antibiotic risk will be performed if there were incidents in recruitment; will allow obtaining results with 194 patients recruited.Ethics and dissemination The study has obtained the authorisation from the Spanish Regulatory Authority, the approval of the ethics committee and the agreement of the directors of each centre. Data will be published in peer-reviewed journals.Trial registration number NCT05394298.